Assumptions of small‐scale intermodal transport - Jaržemskis, Andrius (Transport, 2008)
The aim of the article is to present the alternative to the very well known hub and spoken approach to intermodality when freight scale is small. When usually the blocked trains operate between two big intermodal hubs, here the concept of on‐line blocking of intermodal transport units (ILU) is presented. The article investigates functional interrelations between the carriage of on‐line blocked ILU and the structure of transport network. In order to forecast the flows of on‐line blocked ILU the indirect model has been chosen which enables us to evaluate two important aspects: the first one is the evaluation of the structure of the ILU origins in terms of production and consumption regions as well as the other factors determining the formation of flows of goods. The second one is concerned with the structure of the transport network. Assumption of small‐scale intermodal transport along Berlin‐Baltic intermodal axis is presented. First published online: 27 Oct 2010